Microbial Quality and Prevalence of Water Adulteration of Pasteurized Milk Marketed in Addis Ababa, Ethiopia - Hiwot Tadesse; Aynadis Tamene; Gulelat Dessie (Journal of Pure and Applied Microbiology)
Milk is an important part of human nutrition, especially for children, and is rich in proteins, essential fatty acids, vitamins, minerals, and biofunctional elements. Despite its benefits, milk is prone to microbial contamination due to its composition and handling. Therefore, this study focused on assessing the microbial levels and the frequency of water adulteration in pasteurized milk samples from Addis Ababa, Ethiopia, which represents a critical market for dairy products. A total of 66 pasteurized milk samples from various brands across all sub-cities of Addis Ababa were analyzed. Microbial quality was evaluated using Total Bacterial Count (TBC), Total Coliform Count (TCC), Escherichia coli, and Salmonella detection. Density analysis was conducted to detect water adulteration. Additionally, handling practices at retail were assessed through a questionnaire survey. A considerable portion of pasteurized milk samples exhibited deviations in density from Ethiopian (31.6%) and East African standards (18.3%), suggesting potential water adulteration. Microbial analysis revealed that while all samples met TBC (100%) and E. coli (100%) standards, a notable proportion exceeded the TCC (88%) limit, thereby indicating inadequate processing or post-pasteurization contamination. Salmonella (98%) was absent in most samples tested. Overall, this study underscores critical issues with pasteurized milk quality in Addis Ababa, including frequent water adulteration and elevated microbial contamination, which pose risks to both nutritional value and consumer health. Therefore, strengthening quality control measures and enhancing hygiene practices throughout the dairy distribution chain are imperative to guarantee milk safety and compliance with international standards.